S2 Fluorescence Dynamics of meso‐Aryl‐Substituted Subporphyrins1. Issue 48 (25th October 2013) - Sung, Jooyoung; Kim, Pyosang; Saga, Shun; Hayashi, Shin‐ya; Osuka, Atsuhiro; Kim, Dongho
<x xml:space="preserve">Abstract</x> S2 Fluorescence: Subporphyrins are intriguing compounds, but the behavior of their higher excited states has not been studied thus far. The S2 fluorescence of subporphyrins has now been investigated; internal conversion from the S2 to the S1 state was revealed to occur within approximately 300 fs. The two transition dipole moments of the degenerate S2 states are orthogonally oriented despite the C3 symmetry of the subporphyrin.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>